ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PEMBAGIAN DIVIDEN PADA PERUSAHAAN YANG TERGABUNG DALAM INDEX JII DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Eveilin Rosalina Putri; Moh. Amin; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThis study aims to determine the factors that influence the dividend distribution policy. The population in this study are companies listed on the Indonesia Stock Exchange. The sample used is the company incorporated in the index JII. The technique used in sampling is Purposive Sampling technique, the sample chosen was 30 companies. Data is taken using the documentation method. The data analysis method used is multiple regression analysis with the help of SPSS version 14 software (Product Statistics and Solution Services version 14). The test data used is the simultaneous hypothesis test (f), determination coefficient (R2), and partial hypothesis test (t). that decision of this study shows that simultaneously the independent variables have a Significant influence on the dependent variable. According to the test results of the coefficient of determination, the value of R Square is 50.2% while the remaining 49.8% is influenced by other variables not included in this study. Based on the results of the partial test all variables have an influence on dividend distribution, return on equity (ROE) (sig = 0.029), debt to equity ratio (DER) (sig = 0.038) and cash ratio (sig = 0,000) has an influence on dividend distribution. Keywords: cash ratio, (ROE), (DER), and dividend payout ratio.Keywords: cash ratio, return on equity (ROE), debt to equity ratio (DER), and dividend payout ratio